Template-Assisted Self-Assembly of Conductive Polymer Electrodes for Ionic Electroactive Polymers - Jo, Andrew; Huet, Clémence; Naguib, Hani E. (Frontiers in Bioengineering and Biotechnology, 2020)
Ionic electroactive polymers (EAP) can greatly aid in biomedical applications where micro-sized actuators are required for delicate procedures. Since these types of actuators generally require platinum or gold metallic electrodes, they tend to be expensive, susceptible to wear and tear, and have limited actuation strains. In this study, Nafion is used for the polymeric actuating membrane and is sandwiched between two self-assembled electrodes made from conductive polymers (CP) which allow for a cost-effective fabrication and can theoretically achieve higher actuation strains as they are not constrained to metallic electrodes. This study presents a novel method for fabrication of polymeric actuators made from Nafion by treating the surface of Nafion precursor membrane with NaOH to activate its surface without activating its core. Roughening of the membrane is not required to improve the adhesion between the electrodes and the membrane as the polymeric electrodes interlock with the Nafion membrane at the interfacial layer during the polymerization of CP electrodes. By adjusting concentration and the time of the surface activated fabrication treatment (SAFT), we can control the interfacial layer’s thickness and the polymeric electrode’s growth pattern. The electrodes in this study are made from either polyaniline (PANI) or poly(3,4-ethylenedioxythiophene) (PEDOT) and the SAFT duration allows for PANI electrodes to grow linearly, orthogonally, or randomly along the Nafion surface. The formation of these electrodes is verified by standard electron microscopy (SEM) and by the decrease in sheet resistance after each polymerization cycle. The EAPs that were made with PEDOT shows some negative deformation at the start of actuation. This observation was not found in the actuators made with PANI. Both PANI and PEDOT showed higher actuation strains than the typical all polymeric ionic EAPs and so this fabrication method may be beneficial in the development of grippers for neurosurgical applications.